Gastric emptying of non digestible solid radiopaque markers and autonomic neuropathy in chronic liver disease - A. Kemal GÜRBÜZ; Levent DEMİRTÜRK and Selahattin HÜLAGÜ and E. KIZILKAYA and S. GÜL and E. KOÇER and M. DANACI and Z. ÇANKIR (Turkish Journal of Gastroenterology, 2020)
-